Boron nitride honeycombs with superb and tunable piezopotential properties. (November 2017) - Zhang, Jin
Abstract: Exploring new piezoelectric nanomaterials (PNMs) with unique piezoelectric and piezopotential properties plays a crucial role in designing novel piezotronics nanodevices. In this paper, using hybrid finite element-molecular dynamics simulations, we find a remarkable piezopotential property in the recently proposed boron nitride honeycomb (BNHC) structures. Our results show that, due to their unique polarization distribution BNHCs possess a tensile piezoelectricity in the armchair direction and a shear piezoelectricity in the zigzag direction. It is expected that such a combination of tensile and shear piezoelectricity in BNHCs render them have the ability to harvest almost all types of mechanical energies in the ambient environment. Moreover, the elastic constant, the piezoelectric coefficient and the dielectric constant of BNHCs are found to decrease when their cell length increases, which makes the piezopotential coefficients of BNHCs significantly increase in this process. This observation indicates that the piezopotential properties of BNHCs can be efficiently tailored by adjusting their cell length. As for BNHCs with a proper cell length, we find that their specific piezopotential coefficients can become much larger than those of most existing PNMs. In addition to the remarkable piezopotential properties, a large failure strain is also observed in BNHCs. Such high specific piezopotential coefficients and failure strain in BNHCs render them appealing in the design of novel piezotronics nanodevices with ultralight weight and ultrahigh stretchability. Graphical abstract: Highlights: Piezopotential of boron nitride honeycombs (BNHCs) is studied by FE-MD simulations. BNHCs possess a combination of tensile and shear piezoelectricity. Piezopotential properties of BNHCs can be tailored by adjusting their cell length. BNHCs possess extremely high specific piezopotential coefficients.